Representation of the Community Share Ownership Trust programme in print media analysing power relations between public and private newspapers: A study of The Herald and the Zimbabwe Independent, from 23 January to 18 October 2014. - Mratu, Zvakarongwa (Midlands State University, 2020)
The study start out to determine the role of language in the strategic representation of the Community Share Ownership Trust programme particularly the case of the Zimbabwe Independent and The Herald issues from 23 January to 18 October 2014. The research intended to analyse language used in the selected print media articles with specific focus on highlighting how it was manipulated by reporters of both newspapers to advance their ideological inclinations. The findings of the study reveal that the private and public newspapers contest for power through fundamentally divergent representation of the same programme. The Zimbabwe Independent affiliates with the opposition parties in a bid to advance their partisan interests. Therefore they expose a negative attitude towards the programme by representing it as impractical and irrational. On the contrary, The Herald positively represents the same programme as useful, legitimate and a vehicle for government empowerment.